2010
DOI: 10.1103/physrevb.81.144111
|View full text |Cite
|
Sign up to set email alerts
|

Depth-dependent ordering, two-length-scale phenomena, and crossover behavior in a crystal featuring a skin layer with defects

Abstract: Structural defects in a crystal are responsible for the "two-length-scale" behavior in which a sharp central peak is superimposed over a broad peak in critical diffuse x-ray scattering. We have previously measured the scaling behavior of the central peak by scattering from a near-surface region of a V 2 H crystal, which has a first-order transition in the bulk. As the temperature is lowered toward the critical temperature, a crossover in critical behavior is seen, with the temperature range nearest to the crit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
8
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 23 publications
3
8
1
Order By: Relevance
“…Performing several simulations of systems with different sizes and using finite size scaling, we are able to measure the critical exponents characterizing the transition. The critical exponents found are comparable with exponents that have been measured experimentally in a variety of materials, and for different types of transitions [1,2,[7][8][9][10][11][12][13][14]. Notably, similar critical exponents have recently been measured for the magnetic ordering transition that accompanies the onset of the pseudogap state in high T c superconductors [15][16][17][18].…”
supporting
confidence: 83%
See 3 more Smart Citations
“…Performing several simulations of systems with different sizes and using finite size scaling, we are able to measure the critical exponents characterizing the transition. The critical exponents found are comparable with exponents that have been measured experimentally in a variety of materials, and for different types of transitions [1,2,[7][8][9][10][11][12][13][14]. Notably, similar critical exponents have recently been measured for the magnetic ordering transition that accompanies the onset of the pseudogap state in high T c superconductors [15][16][17][18].…”
supporting
confidence: 83%
“…Assuming the defects are arranged in walls extending in the y direction with the lines parallel to z, it is found that the local relative critical temperature change τ c ( r) is(1) where r is the normal vector pointing from the closest dislocation line, b is the magnitude of the Burgers vector, l is the unit of length used, ν is Poisson's ratio, h is the local average distance between defects, T ′ c ( r) is the local transition temperature and T c is the transition temperature for a defect-free crystal. This results in inhomogeneous ordering in which ordered regions nucleate and grow in the vicinity of the dislocation lines via the addition of quasi 2-D layers around nuclei with the shape of narrow cylindrical rods [1]. Here we study the universal critical scaling properties of this ordering process.To identify the essential physics that controls the scaling properties of this ordering behavior, we studied a zero-field 3D Ising model on a simple cubic lattice with periodic boundary conditions and nonconstant coupling J ij between nearest neighbor spins i and j.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The length scale for the skin effect is about 10 μm, which is very difficult to simulate numerically and surprisingly large. Possibly these effects result from coupling to dislocations at the surface as recently suggested for the phase transition of hydrogen in vanadium [225].…”
Section: Summary Future Experiments and Conclusionmentioning
confidence: 89%